A Systematic Review of Symptom Assessment Tools for Patients with Heart Failure - LI Jingjing, ZHENG Gaigai, WANG Yu, LIU Yancun, ZHANG Shuangqi, YANG Qiaofang (Zhongguo quanke yixue, 2024)
Background There are many tools for symptom assessment of patients with heart failure, but there is a lack of standardized evaluation studies on the quality of such tools, which brings difficulties to the selection of tools. Objective To evaluate the measurement property and methodological quality of symptom assessment tools in patients with heart failure, and to provide reference for relevant personnel to choose symptom assessment tools. Methods The Chinese and English databases such as PubMed, Embase, and CNKI were searched for relevant studies from the date of library construction to July 30, 2023. The Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN) guideline was employed to evaluate the scale and form recommendations. Results Eleven studies were included for quality assessment, including eight tools for assessing symptoms in patients with heart failure: Chinese version of Memorial Symptom Assessment Scale Heart Failure (MSAS-HF), Heart Failure Somatic Perception Scale (HF-SPS), M.D.Anderson Symptom Inventory Heart Failure (MDASI-HF), Symptom Status Questionnaire Heart Failure (SSQ-HF), Shortness of Breath in Heart Failure Instrument (SOB-HF), Minnesota Living with Heart Failure Questionnaire (MLHFQ), Chronic Heart Failure Assessment Tool (CHAT) and Kansas City Cardiomyopathy Questionnaire (KCCQ). Regarding the measurement property, scales such as Chinese version of MSAS-HF, MDASI-HF, MLHFQ, and KCCQ were demonstrated a "sufficient" level of content validity. Conversely, HF-SPS, SSQ-HF, and SOB-HF were exhibited an "uncertain" level of content validity, while CHAT was categorized as having "insufficient" content validity. Finally, Chinese version of MSAS-HF and MLHFQ were recommended as level A, and the other six scales were recommended as level B. Conclusion Certainly, both Chinese version of MSAS-HF and MLHFQ demonstrate a remarkable level of reliability. Considering the distinct attributes of assessment tools, it is highly advisable to utilize Chinese version of MSAS-HF for the purpose of symptom assessment in patients suffering from heart failure.